Bimbingan Firman Tuhan Kepada Jemaat GKSI Yesyurun Senyamuk Tentang Pentingnya Ibadah - Helsina Koen; Haleti Hulu (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
A number of congregations at GKSI Yesyurun Senyamuk show a tendency to not be active in worshiping regularly. This phenomenon needs serious attention so that the congregation can once again appreciate and feel the importance of worship in their lives. One of the main causes of inactivity in worship is the busyness of daily life which increasingly dominates the congregation's attention. This busyness is often a reason that is considered valid for not attending church services. Meanwhile, the method used is qualitative based on direct observation of the phenomena that occur at GKSI Yesyurun Senyamuk. Apart from that, guidance was provided on the word of God to the GKSI Yesyurun Senyamuk congregation, explaining "what is the importance of worship?", "which basis of God's word discusses worship?", "what is the correct way to worship?". The findings from this research have resulted in positive changes in the life of the GKSI Yesyurun Senyamuk congregation, such as increasing activeness in worship and changing lifestyles that are more focused on God. This shows that correct worship not only has a spiritual impact, but also socially, strengthening the commitment to live according to God's will.